Transcriptome profiling of Nile tilapia (Oreochromis niloticus) identifies candidate genes in response to riverine pollution - Bijay Kumar Behera; Chirasmita Nayak; Ajaya Kumar Rout; Smruti Priyambada Pradhan; Pranaya Kumar Parida; Dhruba Jyoti Sarkar; Basanta Kumar Das; Anil Rai (Current Research in Biotechnology, 2024)
To delineate the response mechanism of Nile tilapia (Oreochromis niloticus) to the riverine pollution of river Ganga, a comparative transcriptomic analysis was performed utilizing fresh liver through RNA-Seq technology. A total of 51.39 million and 32.8 million reads were obtained after excluding low quality sequences from non-polluted (Barrackpore) and polluted (Kanpur) sites of Nile tilapia. About 81.4 % and 95.3% reads were perfectly mapped with the reference sequence of O. niloticus. Transcriptional analysis generated 363 differential expressed genes (DEGs) including 131 up-regulated and 232 down-regulated genes. Gene Ontology (GO) enrichment analysis revealed that significant DEGs were associated with ribosome biogenesis, alpha-amino acid metabolic process, translational initiation etc. as biological process (BP); unfolded protein binding, vitamin binding, carboxylic acid binding and etc. as molecular function (MF); ribosome, and ribosomal subunit as cellular component (CC). The KEGG analysis indicated that these DEGs were highly involved in ribosome, Lysine degradation and RNA transport pathways. Additionally, ten hub genes participated in Translation, Ribonucleoprotein complex biogenesis as BP, Ribosome, Eukaryotic translation initiation factor 3 complex as CC and Structural constituent of ribosome, RNA binding as MF were affected in riverine pollution. Overall, this transcriptome investigation provided an extensive overview of pollution triggered transcriptional mechanisms in Tilapia liver and would be highly significant for further exploration of the molecular processes in response to pollution.